Postharvest Technology of Fruits and Vegetables: An Overview - Singh, Vishal; Hedayetullah, Md; Zaman, Parveen; Meher, Jagamohan (Journal of Postharvest Technology, 2014)
Harvested fruits and vegetables require adequate and advanced postharvest processing technologies for minimizing the qualitative as well as quantitative losses after harvesting. Nearly 40% fruits and vegetables are wasted every year due to improper handling, storage, packaging, and transportation. Wastage of fruits and vegetables in huge amount due to un-implementation of advance postharvest technological approaches also reduces the per capita availability of fruits and vegetables. Intensive emphasis is required to develop the advance postharvest technologies for improving the global food security by enriching the economy of agricultural produce of the world with minimal losses of consumable fruits and vegetables. The present article discusses the common yet important postharvest technologies to maintain the quality of fruits and vegetables.